The effect of breathing action on velocity in front crawl swimming - Pedersen, T.; Kjendlie, P. L. (Biomechanics and Medicine in Swimming X, 2006)
Ten competitive, national level adult swimmers (age 25 ± 3 years (mean ± SD) swam three 25m freestyle sprints with different breathing patterns in randomised order to examine how breathing actions influence velocity during a 25m front crawl sprint. Velocity measurements were carried out using a computerized swimming speedometer and data from mid-pool free swimming (10-20m) was extracted. There was no significant difference in mean (±SD) velocity (v) between sprinting with one breath (v=1.74±0.14 m_s-1) compared to no breath (v=l.73+0.14 m_s-1). There was a significant (p<0.05) reduc-tion in velocity when breathing every stroke cycle (v=1.70±0.14 m_s-1), compared to both no breath and one breath trials. Swimmers should breathe as little as possible during 50m freestyle races and breathe no more than every 3rd stroke cycle during a 100m freestyle race.